Forensic Linguistics Studies in Netizen Comments on the 2024 Vice Presidential Debate Gimmick on Facebook/Twitter - Wahyuni, Rani Sri (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
Research is based on the presence of symptoms that are widely discussed by the public about some of the gimmicks used and contain certain meanings presented by one of the presidential candidates during the presidential candidates' debate in 2024. The use of the gimmick triggered many comments and caused many interpretations. This study aims to find or study some violations in the use of language on social media Facebook/Twitter in comments related to gimmick-gimmick used at a debate that contains the meaning of words/sentences demeaning and insinuating. The research method used is descriptive qualitative. Data is collected using a refer and record technique. The results showed that in the form of speech acts considered demeaning/insulting there were 20 speeches, in Stirum/Diseufeumism there were 10 speeches. The most common form of speech acts found is a demeaning/insulting and insinuating speech act of 10 data.  Meanwhile, the least acts of speech that appeared in the 2024 vice presidential debate, namely the adverse speech acts.Keywords: forensic linguistics; gimmick;language use